SP0161 Functional Consequences of Anti-Pad-Antibodies in RA. (10th June 2014) - Darrah, E.
Abstract : Peptidylarginine deiminase (PAD) enzymes have emerged as key participants in the pathogenesis of rheumatoid arthritis (RA) due to their expression in inflamed RA synovium and generation of citrullinated autoantigens, hallmark targets of the immune response in RA. Autoantibodies to PAD4, a nuclear member of this enzyme family, are present in 35% of RA patients and are associated with more erosive joint disease. Interestingly, soluble PAD4 has been detected in the synovial fluid of inflamed joints, and has been postulated to possess extracellular citrullination activity. However, the calcium availability in the joint is estimated to be 0.5-1.0mM, far less than the 5-10mM calcium required for PAD4 activity in vitro . Functional studies of PAD4 enzymatic activity have revealed heterogeneous effects of autoantibody binding on the citrullination of small molecule and protein substrates at supraphysiologic calcium concentrations. Results: We have recently described a subset of PAD4 autoantibodies, present in 12-18% of RA patients, that cross-react with the related enzyme PAD3, and have unique biochemical and clinical properties. In functional assays measuring citrullination of the PAD4 substrate, histone H3, cross-reactive antibodies had the striking ability to enhance PAD4 enzymatic activity up to 400-fold at physiologic calcium concentrations (0.2-1.0mM). Cross-reactive antibodies lowered the amount of calcium required for half maximal PAD4 activity from 3.3 to 0.5mM, well into the physiologic range. This effect was mediated by autoantibody binding to a region of PAD4 which normally undergoes calcium-induced structural changes necessary for citrullination of target proteins. A pathogenic role for these PAD4-activating antibodies was suggested by the finding that RA patients with cross-reactive antibodies had the most severe and progressive joint disease compared to patients who lacked this subset. In addition, cross-reactive antibody positive patients were at the highest risk for the development of RA-associated interstitial lung disease, an effect augmented by cigarette smoking. Conclusions: Taken together, this work describes a potentially pathogenic subset of PAD4 autoantibodies with the capacity to drive the production of autoantigens in RA and identifies patients who may benefit from the addition of novel PAD-inhibitor therapies. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6169